Waste Cockle Shell As Potential Catalyst In Production Of Biodiesel From Used Cooking Oil - Syadatul Adawiyah Binti Johar (2021)
The aim of this study is to investigate the potential use of waste cockle shell as catalyst in production of biodiesel via transesterification from used cooking oil (UCO). UCO undergo pre-treatment to discard any impurities. Waste cockle shell was crushed into fine powder, sieved to 0.045 mm particles and divided into natural and calcined cockle. Waste cockle shell was calcined at 900*C for 2 hours. Analysis of FTIR and XRD were conducted to determine the functional group and the element of powder waste cockle shell. The results confirmed the formation of calcium oxide (CaO) from calcined cockle shell due to decomposition of calcium carbonate (CaCO3) from natural cockle shell. Besides that, the surface morphology and surface area of natural and calcined cockle shell was illustrated by SEM and BET. The higher calcination temperature gives smoother, aggregated at the surface and provide high specific surface area. Thus, more carbon dioxide will be released to give the more conversion to CaO. Then, the optimization of transesterification was investigated using the effect of alcohol to oil ratio, separation time, types of alcohol used, catalyst loading and different used of catalyst. The optimum result displayed a 1:1 alcohol to oil ratio, 48 hours' separation time, ethanol used, 4 g catalyst and 60*C reaction temperature within 1 hour. The yield of biodiesel from natural and calcined cockle shell were compared. Natural cockle shell produced 56% yield of biodiesel whilst calcined cockle shell produced 65%. The components of biodiesel obtained were identified using gas chromatography-mass spectrometry (GC-MS). Production of biodiesel from used cooking oil using waste cockle shell particularly relevant as it can solve the environmental problem caused by fossil fuel use and reduced the biofuel industry production cost. Keywords: Waste cockle shell, heterogeneous catalyst, calcination, transesterification, used cooking oil.